SHYNESS DITINJAU DARI POLA ASUH OTORITER ORANG TUA PADA SISWA-SISWI SMA DI METHODIST-2 MEDAN - Sarinah Sarinah (Universitas Negeri Medan, 2017)
This study aims to examine the relationship between the authoritarian parenting by parents and shyness. The hypothesis of this study is that there is a positive relationship between authoritarian parenting and shyness, assuming the higher the authoritarian parenting, the higher the shyness and conversely the lower the authoritarian parenting, the lower the shyness. Subjects of this study are tenth grade students of SMA Methodist-2 Medan as many as 240 people with cluster sampling method. Data are obtained from a scale to measure authoritarian parenting and shyness. The calculation is performed by assumption test that consists of normality test of distribution and linearity test of relationship. The data analysis used is product moment correlation through SPSS 17 for Windows. Results of the data analysis show a correlation coefficient of 0.882 with p 0.000 (p < 0.05). The results show there is a positive relationship between authoritarian parenting and shyness. Authoritarian parenting is one of the factors that affect shyness by contribution (R2) of 77.8 percent and the remaining of 22.2 percent is affected by other factors not examined. In conclusion, the hypothesis of there is a positive relationship between the authoritarian parenting with shyness is accepted.